2018
DOI: 10.1177/1744806918763646
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Gi/O-coupled receptors in somatosensory neurons: Potential therapeutic targets for novel analgesics

Abstract: Primary sensory neurons in the dorsal root ganglia and trigeminal ganglia are responsible for sensing mechanical and thermal stimuli, as well as detecting tissue damage. These neurons express ion channels that respond to thermal, mechanical, or chemical cues, conduct action potentials, and mediate transmitter release. These neurons also express a large number of G-protein coupled receptors, which are major transducers for extracellular signaling molecules, and their activation usually modulates the primary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 154 publications
2
35
0
1
Order By: Relevance
“…After recording the basal RA-MA currents, the cells were treated with 25 µM baclofen for 3 mins and RA-MA currents were re-recorded for comparison. As expected, activation of GABAB receptors also potentiated Piezo2 currents almost 2-fold ( Figure 1C-E), in 59 % of the neurons, and had no effect in 41%% of DRG neurons tested ( Figure 1F) probably because not every DRG neuron co-expresses GABAB1 and GABAB2 receptors and the obligatory heterodimerization of these receptors is required for proper Gprotein signaling (Padgett and Slesinger, 2010;Yudin and Rohacs, 2018). In both protocols, baclofeninduced potentiation was long lasting and persisted for several minutes after removal of the agonist ( Fig.…”
Section: Gabab Receptor Activation Potentiates Piezo2-like Currents Isupporting
confidence: 72%
See 3 more Smart Citations
“…After recording the basal RA-MA currents, the cells were treated with 25 µM baclofen for 3 mins and RA-MA currents were re-recorded for comparison. As expected, activation of GABAB receptors also potentiated Piezo2 currents almost 2-fold ( Figure 1C-E), in 59 % of the neurons, and had no effect in 41%% of DRG neurons tested ( Figure 1F) probably because not every DRG neuron co-expresses GABAB1 and GABAB2 receptors and the obligatory heterodimerization of these receptors is required for proper Gprotein signaling (Padgett and Slesinger, 2010;Yudin and Rohacs, 2018). In both protocols, baclofeninduced potentiation was long lasting and persisted for several minutes after removal of the agonist ( Fig.…”
Section: Gabab Receptor Activation Potentiates Piezo2-like Currents Isupporting
confidence: 72%
“…Gi-coupled receptor activation leads to the dissociation of the trimeric G-proteins: Gαi and Gβγ. Since most of the documented effects on ion channels after activation of the Gi-signaling pathway are attributed to Gβγ (Yudin and Rohacs, 2018), we tested if the regulation of Piezo channels was mediated by Gβγ. We showed that co-expression of βARKct, which chelates Gβγ, abolished both the potentiation of Piezo2, and the inhibition of Piezo1, after activation of Gi-coupled receptors ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to functional and structural homologies of their α subunit, heterotrimeric G-proteins are divided into four types (Gα s , Gα i/o , Gα q/11 , and Gα 12/13 ). Each Gα defines the unique Gαβγ mediated cellular responses [1,[13][14][15][16]. Gα s and Gα i subfamily members are involved in the modulation of the intracellular second-messenger cAMP levels, either stimulating (G s ) or inhibiting (G i ) the production of cAMP by AC activity.…”
mentioning
confidence: 99%